Structural and In Vitro Functional Comparability Analysis of Altebrel™, a Proposed Etanercept Biosimilar: Focus on Primary Sequence and Glycosylation - Ramin Fazel; Yudong Guan; Behrouz Vaziri; Christoph Krisp; Laura Heikaus; Amirhossein Saadati; Siti Nurul Hidayah; Manasi Gaikwad; Hartmut Schlüter (MDPI AG, 2019)
The demand for reliable comparability studies of biosimilars grows with their increased market share. These studies focus on physicochemical, structural, functional and clinical properties to ensure that a biosimilar has no significant differences to the originator product and can be released into the market without extensive clinical trials. In the current study, Enbrel® (etanercept, the originator) and Altebrel™ (the proposed biosimilar) underwent direct comparison. “Bottom-up” mass spectrometric analysis was used for primary sequence analysis, evaluation of N/O-glycosylation sites and quantification of methionine oxidation. N/O-glycans were analyzed after permethylation derivatization and the effect of N-glycans on in-vitro functionality of etanercept was assayed. Three enzyme peptide mapping resulted in complete identification of the primary structure. It was confirmed that total ion chromatograms are valuable datasets for the analysis of the primary structure of biodrugs. New N/O-glycan structures were identified and all the N-glycans were quantified. Finally, investigation of the functional properties of N-deglycosylated and non-modified etanercept samples using surface plasmon resonance analysis and in-vitro bioassay showed that N-glycosylation has no significant effect on its in-vitro functionality. Analysis of etanercept and its biosimilar, revealed a high similarity in terms of glycosylation, primary structure and in-vitro functionality.